Peningkatan Kapasitas Pegawai Melalui Program Hospital Disaster Plan (HDP) di RSUD dr. Loekmono Hadi Kabupaten Kudus - Ficky Adi Kurniawan; Anggoro Budi Prasetyo; Oktomi Wijaya (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
This research aims to see the results of employee capacity building activities through the Hospital Disaster Plan (HDP) program at RSUD dr. Loekmono Hadi Kudus Regency. Hospital preparedness plans are very important in ensuring the safety of the hospital environment and the actions that need to be taken to ensure health services remain available during a disaster situation. Dr. Hospital Loekmono Hadi needs to develop a hospital preparedness plan. The methods used in hospital employee empowerment activities include pretest-posttest, lecture-discussion, direct training/practice, observation and evaluation methods. The research results show that Disaster Management at RSUD dr. Loekmono Hadi is very important considering that Kudus Regency has a variety of potential disasters and is located in an area that has potential threats of flooding, drought, landslides and earthquakes. there was an increase in pretest and posttest results by 12.00 points. It is felt that activities to strengthen employee capacity through the Hospital Disaster Plan (HDP) program need to be developed further because hospitals need more preparedness capacity in facing disasters or emergency situations and can support home accreditation.